Tissue-specificity of liver gene expression: a common liver-specific promoter element. - Kugler, W (1988)
Several liver specific genes contain a sequence similar to the hepatocyte-specific promoter element (HP1) identified in the Xenopus albumin gene. By competition experiments in gel retardation assays we demonstrate that the albumin, the alpha 1-antitrypsin and the beta-fibrinogen promoter elements bind an identical factor, whereas the HP1-related sequence in the transferrin gene has different binding properties. The elements of all four genes are able to confer increased transcription in nuclear extracts from rat liver. The HP1 found in the albumin, alpha 1-antitrypsin and beta-fibrinogen promoter bind identical transcription factors, since in vitro transcription can be specifically inhibited by the addition of an excess of the corresponding oligonucleotide. The cis-element HP1 and its transacting factor have been conserved during evolution, since elements derived from frog, rat and human genes function in rat liver nuclear extracts.